The Effect of Class Management on Economic Learning Motivation at SMA Negeri 20 Palembang - Erma Yulaini; Diana Widhi Rachmawati; Devi Nur Ahini Oktavia Putri; Nyoman Tri Chayanti (International Journal on Advanced Science, Education, and Religion, 2021)
The purpose of this study was to determine the effect of classroom management on motivation to study economics at SMA Negeri 20 Palembang for the 2019/2020 academic year. The research method used quantitative descriptive method. The sample in the research of class X amounted to 54 students. In collecting data the researchers used techniques of documentation and questionnaires. The results showed that the class management had a significant effect on the economic learning motivation received with a large effect from the class management of 31.97%, while the remaining 68.03% was influenced by other factors. Therefore, classroom management is needed in the learning process. Keywords: Classroom Management, Learning Motivation, Management Education